Knowledge and perceptions of men towards vasectomy among men of reproductive age in Otuke District- Uganda - Anna Grace Auma; Emmanuel Madira; Beth Namukwana; Ronald Izaruku; Amir Kabunga; Tamrat Endale WMichael (Contraception and Reproductive Medicine)
Abstract Objective This study aimed to assess knowledge of and perceptions towards vasectomy as a family planning method among men of reproductive age in rural northern Uganda”. Methods A cross-sectional study involving 624 participants was conducted. Sociodemographic characteristics, use of vasectomy, number of children, and knowledge of vasectomy were assessed. Perceptions of vasectomy were measured, focusing on cultural, religious, and gender-related aspects. Results The study revealed a predominantly adult, married, and Catholic population with low educational attainment. 2% of participants had used vasectomy as a family planning method, this indicates the right to preference in choosing vasectomy as a family planning method. Approximately half of the participants demonstrated awareness of vasectomy, and negative perceptions were recorded, with 63.5% expressing their opinions. Cultural and religious beliefs, along with concerns about promiscuity, play a significant role in shaping the perceptions. The majority believed in male dominance in family planning decisions, and a considerable portion endorsed sterilization exclusively for women. Conclusion This study highlights the low utilization and negative perceptions of vasectomy among men in rural northern Uganda, emphasizing the need for targeted interventions to address cultural and religious misconceptions and enhance education on family planning options. Public health campaigns should focus on dispelling misconceptions about vasectomy, particularly addressing cultural and spiritual concerns. Educational programs should target men and their communities, emphasizing the benefits of shared family planning decisions. Further research incorporating qualitative methods could provide a deeper understanding of the cultural aspects influencing vasectomy perceptions in this population.